Định giá kinh tế chương trình chống xói mòn bờ biển: nghiên cứu trường hợp Hội An - Nguyen Manh , Hung; Nguyen Thi Lan , Anh; Nguyen , Tuan (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2020)
The paper uses discrete choice experiment (DCE) and mixed logit model to evaluate the coastal erosion protection program in Hoi An, a world heritage city that is under the severe impact of erosion. We designed and constructed a new database for research targeting local households and their awareness on risk of coastal erosion. Research results show that residents in Hoi An support the construction of protective structures along the coast, prefer to visit a wide beach with multiple utilities and free access. From the results of individuals’ preference and willingness to pay (WTP) for the erosion protection program, the paper suggests a proposal for developing an effective and sustainable erosion protection policy using local contributions. To the best of our knowledge, this is the first study in economic valuation of coastal erosion policy in Vietnam estimating WTP through the DCE method.